Academic Supervision and Guidance and Counseling Teacher Self-Efficacy at the State Junior High School Level - Amianti Putri Hestiningtyan; Sugiyo; Awalya (International Journal of Education and Humanities, 2021)
There is only one management function involved in the management of advice and counseling, which is controlling (supervision). Supervision is an essential component of the guidance and counseling program. As a result, academic monitoring implemented by both school supervisors and school principals is linked to the professional performance of guidance and counseling teachers. The purpose of this study is to investigate the impact of academic supervision implementation on the professional performance of guidance and counseling teachers using self-efficacy as an intervening variable. This study employs quantitative tools and a correlational research design. The study involved guidance and counseling teachers from the State Junior High School in Pemalang Regency. According to the study's findings, academic monitoring by school supervisors is still not equivalent since the number of school supervisors is still limited compared to the number of schools and teachers in the Pemalang Regency. However, the study's findings also suggest that academic supervision impacts the professional performance of guidance and counseling teachers at SMP Negeri Pemalang Regency. Furthermore, this element of self-efficacy demonstrates that the outcomes have no substantial positive influence. That is, academic supervision does not mediate between Guidance and Counseling teachers' professional performance.